Rethinking Augustine’s Misunderstanding of First Movements: the Moral Psychology of Preliminary Passions - Gao, Yuan (Sophia, 2021)
Augustine’s theory of first movements (primus motus, propatheia, and propassio) has provoked many controversies over the years. When discussing Augustine’s position in preliminary passions, some scholars maintain that he misunderstands the Stoics, whereas some others argue that he grasps their works rather well and his accounts are consistent with Stoic teaching. This article examines how Augustine transforms his predecessors’ conception of first movements into his own theory, with particular focus on whether Augustine misinterprets his predecessor’s doctrine in his approach. The first section introduces the recent disputations on Augustine’s misunderstanding of the Stoic concept of the first movements. The second section compares Augustine’s opinions in his early, middle, and late writings to determine whether changes occur in his interpretation. Based on the above observations, this essay argues that Augustine is familiar with the Stoic doctrines, but in his later works, he ‘deliberately’ deviates from their concept of the first movements in order to refute their ‘pride’ and to defend his Christian position on the psychology of preliminary passions. These deliberate new changes of terms by Augustine do not derive from a misunderstanding, but rather follow from his attempt at constructing a new dynamic theological framework of addressing passions during his later thought. The article concludes with a third section that revisits the modern critiques and responds with a consideration of the significance of Augustine’s views on preliminary passions.